Mentoring the Integrated Non-Communicable Diseases Development Post (Posbindu PTM) "Boulevard" Cadres Together with the Pimpinan Cabang Aisyiyah, Mangkubumi District, Tasikmalaya City in Reducing the Incidence Rate of Obesity and Hypertension - Hana Ariyani; Sulidar Fitri; Suprayogi; Ananta Putra; Destria Nurul Fauzia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Non-Communicable Diseases are still a concern because they cause premature death (before 70 years) in middle and low income countries. The risk factors for this disease include hypertension and obesity. This mentoring program aims to increase the capacity of cadres to help control hypertension and obesity not only in the context of checking blood pressure and body weight and height but also in providing education about the importance of reducing hypertension and obesity rates as risk factors for NCDs. The method used in this Community Service program is Community-Based Research (CBR), namely providing health education accompanied by a pre-test and post-test before and after the health education activity. This program was attended by 10 cadres as part of the Pimpinan Cabang Aisyiyah, Mangkubumi District, Tasikmalaya City and 40 Posbindu PTM "Boulevard" participants. Based on the results of the analysis of pre-test and post-test answers which assess knowledge about Obesity and Hypertension, it can be concluded that the health education "Knowing Obesity and Hypertension" is effective in increasing knowledge about the importance of preventing and controlling Obesity and Hypertension.